Plywood - 8096 British Standards Institution (London : British Standards Institution, 1985)
Pt.1. Specification for construction of panels and characteristics of plies including marking -- pt.2. Glossary of terms -- pt.3. Specification for acceptance levels for post - manufacture batch testing including sampling -- pt.4. Specification for toleranceces on the dimensions of plywood panels s -- pt5. Specification for moisture content -- pt.6. Specification for limits of defect for the classification of plywood by appearance -- pt.7. Specification for classification of resistance to fungal decay and wood borer attack -- pt.8. Specification for bond performance of veneer plywood